Training in Deontological Requirements of Interpreters Dealing with Refugees: International Protection as an Opportunity for Social Entrepreneurship in Translation and Interpreting Studies in Spain - Martín-Ruel, Estela (HERMES - Journal of Language and Communication in Business, 2020)
Having noted the entrepreneurial reluctance of graduates in general and T&I graduates in particular in Spain, we propose social entrepreneurship in the field of international protection and refugees as a potentially viable employment opportunity. The ever-growing number of asylum seekers arriving in Spain have a recognised right to access translation and interpreting services, and we therefore advocate the training of interpreters to operate in asylum scenarios and meet the specific deontological requirements involved therein. Future professionals need to be equipped with all the tools necessary to be able to handle the different challenges that may arise in such situations. To this end, we present the results of a series of interviews conducted with refugee reception organisations in the province of Seville, the capital of Andalusia which is one of the regions in the EU which handles the highest number of immigrant arrivals. The situations experienced in these organizations may reflect the state of the question in the asylum field. We found that the application of professional ethics in real-case situations is indeed very often deficient, and its inclusion in training syllabuses in the country could help address this social need.